New additions to the myxobiota of Costa Rica - Rojas Alvarado, Carlos Alonso (2015)
The most recent checklist of myxomycetes from Costa Rica reported 208 species for the country. Informational gaps detected in that work and a sustained survey effort since the publication of the checklist increased the number of species to 218. In the study reported herein, we identified seven species not previously known from Costa Rica. In addition to increasing the number of species recorded to 225, this work also provided important information relating to potential distribution, ecological preferences and the role of isolation techniques for biodiversity surveys of myxomycetes. The fact that a region with only 0.05% of the terrestrial surface of the Earth accounts for approximately 25% of the global biodiversity of myxomycetes, even with the technical limitations of the isolation methods used up to date, shows one more time that this group of organisms is not only well established in terrestrial environments but widely distributed in the Neotropics.